Flora of Ceará Wetlands, Brazil: Zingiberales - Hugo Pereira do Nascimento; Vitor Vasconcelos Magalhães; Lígia Queiroz Matias (Rodriguésia)
Abstract The study aimed to describe the species of Zingiberales in the wetlands of Ceará. Specimens from the herbaria ALCB, EAC, HUVA and HVASF were analyzed. Field work was carried out between 2010 and 2023. As result, we recognize representatives of Cannaceae (Canna glauca) and Marantaceae (Thalia densibracteata and Thalia geniculata) in the Ceará wetlands. The morphological characters that differentiate the three species are the shape of the leaves and the size and color of the flowers. An identification key, morphological descriptions, comments, distribution map, and photographic plates are presented.